Recruitment and retention of clinical trial participants: understanding motivations of patients with chronic pain and other populations - Anastasi, Joyce K.; Capili, Bernadette; Norton, Margaret; McMahon, Donald J.; Marder, Karen (Frontiers in Pain Research, 2024)
This paper aims to present and discuss the issues, challenges, and strategies related to recruitment and retention in clinical trials involving participants with chronic pain. The randomized controlled clinical trial (RCT) is widely regarded as the gold standard for evaluating clinical interventions. However, it is crucial to acknowledge and address the challenges associated with recruiting and retaining participants. To prioritize the experience of the study population, targeted outreach strategies and a patient-centric approach are necessary. Researchers should consider incorporating recruitment and retention strategies during the study design phase. Implementing multi-pronged recruitment methods, leveraging relationships with community providers, and involving representatives of the patient population are helpful approaches. Effective communication and maintaining a professional environment are vital for optimizing engagement and supporting the successful execution of clinical trials involving participants with chronic pain.